Public perceptions of quarantine: community-based telephone survey following an infectious disease outbreak - Rea Elizabeth; Tracy C Shawn; Upshur Ross EG (BMC, 2009)
Abstract Background The use of restrictive measures such as quarantine draws into sharp relief the dynamic interplay between the individual rights of the citizen on the one hand and the collective rights of the community on the other. Concerns regarding infectious disease outbreaks (SARS, pandemic influenza) have intensified the need to understand public perceptions of quarantine and other social distancing measures. Methods We conducted a telephone survey of the general population in the Greater Toronto Area in Ontario, Canada. Computer-assisted telephone interviewing (CATI) technology was used. A final sample of 500 individuals was achieved through standard random-digit dialing. Results Our data indicate strong public support for the use of quarantine when required and for serious legal sanctions against those who fail to comply. This support is contingent both on the implementation of legal safeguards to protect against inappropriate use and on the provision of psychosocial supports for those affected. Conclusion To engender strong public support for quarantine and other restrictive measures, government officials and public health policy-makers would do well to implement a comprehensive system of supports and safeguards, to educate and inform frontline public health workers, and to engage the public at large in an open dialogue on the ethical use of restrictive measures during infectious disease outbreaks.